Social Impact of Myths and Misconceptions About Coronavirus Pandemic in Nigeria - Agbo, Chinedu Cletus (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2021)
This study is about the social impact of myths and misconceptions about coronavirus pandemic in Nigeria. The study has the following objectives: to highlight the myths and misconceptions about the coronavirus; examine major propagators of these myths and misconceptions, highlight the consequent social impact, examine the relationship between the myths and misconceptions and the fight against the coronavirus pandemic. The study employed the descriptive and explanatory design method. Questionnaires in addition to library research were applied for data collection. Primary data sources were used and data analysed using the chi square and correlation statistical tool at 5% level of significance which was presented in frequency tables and percentages. The respondents under the study were 100 online respondents from all the geopolitical zones of the country. Results of the study revealed huge social impact of the myths and misconceptions about the coronavirus pandemic which has also affected its effective fight. It concludes that efforts should be made by the Nigeria Centre for Disease Control (NCDC) and related stakeholders in promoting awareness of this virus for reducing/eradicating the myths and misconceptions around it and effectively fighting the COVID-19 pandemic.